Tachigali amarumayu (Leguminosae), a new species from terra firme forests of Southwestern Amazonia - Huamantupa-Chuquimaco I. (2019)
Tachigali amarumayu, a new species of caesalpinioid legume restricted to terra firme forests in southwestern Amazonia, is described, illustrated, and compared with the morphologically similar species T. prancei, T. rugosa, and T. setifera.